พฤติกรรมการขับขี่รถจักรยานยนต์กับการมีส่วนร่วมในการป้องกันและแก้ไขปัญหาอุบัติเหตุที่เกิดจากการขับขี่รถจักรยานยนต์: กรณีศึกษาชุมชนตำบล ท่ามิหรำ อำเภอเมือง จังหวัดพัทลุง - Khongtong, Phatthanun; sukhon, Somhying (วารสารศรีนครินทรวิโรฒวิจัยและพัฒนา สาขามนุษยศาสตร์และสังคมศาสตร์, 2013)
การศึกษาครั้งนี้เป็นการศึกษาวิจัยเชิงพรรณนาแบบตัดขวางร่วมกับการวิจัยเชิงปฏิบัติการ มีวัตถุประสงค์เพื่อศึกษาพฤติกรรมการขับขี่รถจักรยานยนต์และการมีส่วนร่วมในการป้องกันแก้ไขปัญหาอุบัติเหตุที่เกิดจากรถจักรยานยนต์บนท้องถนน ในการศึกษาครั้งนี้ผู้วิจัยแบ่งการนำเสนอข้อมูลเป็น 2 ส่วน คือ ข้อมูลเชิงปริมาณ ได้จากการศึกษาวิจัยเชิงพรรณนาและข้อมูลเชิงคุณภาพ ได้จากการศึกษาวิจัยเชิงปฏิบัติการในการสำรวจพฤติกรรมการขับขี่รถจักรยานยนต์ เก็บรวบรวมข้อมูลโดยใช้แบบสัมภาษณ์ในประชาชน จำนวนทั้งสิ้น 404 คน ส่วนการศึกษาการมีส่วนร่วมของประชาชนในการป้องกันและแก้ไขปัญหาอุบัติเหตุที่เกิดจากรถจักรยานยนต์บนท้องถนน เก็บรวบรวมข้อมูลจากประชาชนที่เข้าร่วมโครงการ จำนวน 122 คน โดยใช้วิธีการสนทนากลุ่ม สัมภาษณ์เจาะลึก การสังเกต และการถอดบทเรียนจากเวทีประชาคม ตรวจสอบข้อมูลด้วยวิธีสามเส้า วิเคราะห์ข้อมูลจากความสอดคล้องเชิงเนื้อหา ผลการศึกษาสัดส่วนประสบการณ์การเกิดอุบัติเหตุของกลุ่มตัวอย่าง จำนวน 404 คน พบกลุ่มตัวอย่างที่เคยประสบอุบัติเหตุ ร้อยละ 37.6 (95% CI: 31.1–44.0) เป็นเพศชาย ร้อยละ 33.3 (95% CI: 26.5–40.1) เป็นเพศหญิง กลุ่มที่เคยประสบอุบัติเหตุมีคะแนนความรู้เกี่ยวกับกฎหมายจราจรเฉลี่ย 6.2 (95%CI: 6.00–6.4) มีคะแนนเฉลี่ยด้านการขับขี่ปลอดภัย 6.7 (95% CI: 6.52–6.94) ด้านสภาพแวดล้อมในการขับขี่รถจักรยานยนต์ พบมีบริเวณถนนที่มีป้ายเตือน/ป้ายห้าม ร้อยละ 80.5 สัญญาณไฟจราจรเสียบ่อย ร้อยละ 50.6 กลุ่มตัวอย่างที่เคยประสบอุบัติเหตุ สวมหมวกนิรภัยทุกครั้งขณะขับขี่ ร้อยละ 42.8 ปรับแต่งรถจักรยานยนต์ โดยปาดเบาะ ร้อยละ 32 เคยดื่มสุราแล้วขับขี่รถจักรยานยนต์ ร้อยละ 36.9 เคยขับรถฝ่าสัญญาณไฟจราจร ร้อยละ 40.2 ขับขี่รถจักรยานยนต์โดยใช้ความเร็วในช่วงความเร็ว 51-80 km/hr ร้อยละ 69.4 ขับรถโดยไม่พกใบอนุญาตขับขี่ ร้อยละ 80.5 ใช้โทรศัพท์เคลื่อนที่ขณะขับขี่ ร้อยละ 52.0 เทคนิค AIC ใช้ในการศึกษาการมีส่วนร่วมในการป้องกันและแก้ไขปัญหาอุบัติเหตุบนท้องถนนจากรถจักรยานยนต์พบว่า ปัจจัยที่ส่งผลให้เกิดอุบัติเหตุในเขตพื้นที่ตำบลท่ามิหรำ มี 3 ปัจจัย คือ คน รถ และสิ่งแวดล้อม โดยปัจจัยที่สำคัญที่สุดคือ คนไม่เคารพกฎหมายจราจร จากการศึกษาได้พบปัญหาและแนวทางในการแก้ไขปัญหา ได้แก่ ไม่สวมหมวกนิรภัยขณะขับขี่รถจักรยานยนต์ แนวทางแก้ไขคือ ต้องเลือกขนาดของหมวกนิรภัยให้พอดีกับศีรษะของตนเอง และที่สำคัญควรใช้หมวกนิรภัยที่ได้มาตรฐานที่มีเครื่องหมาย มอก. รับรอง ดื่มสุราจนเมาแล้วขับขี่รถจักรยานยนต์แนวทางในการแก้ไข ต้องสร้างจิตสำนึกให้กับประชาชนกลุ่มดังกล่าว ให้มีการรณรงค์สร้างค่านิยมไม่ให้ดื่มสุรา ขับรถโดยไม่มีใบอนุญาตขับขี่ ผู้บังคับใช้กฎหมายต้องมีความพยายามที่จะบังคับใช้กฎหมายให้เข้มงวดมากขึ้น คำสำคัญ: พฤติกรรมการขับขี่รถจักรยานยนต์ การมีส่วนร่วมในการป้องกันและแก้ไขปัญหาอุบัติเหตุ This is a cross-sectional descriptive and action research. The purpose of the study was to examine the behaviors of riding motorcycles and the participation in preventing and solving the problems of road accidents resulting from riding motorcycles. The data was presented in two parts which were quantitative data received from the descriptive research and qualitative data acquired from the action research. The data in the survey of the behaviors of riding motorcycles was collected from 404 participants using the interview. Furthermore, the data in the part of the participation in preventing and solving the problems of road accidents resulting from riding motorcycles was collected from 122 participants joining the project using group discussion, in-depth interview, observation and lesson distilled from civil society forums. The data was tested using triangulation method and analyzed with the credibility of the data. The results of the study were as follows. 37.6 percent (95% CI: 31.1-44.0) of 404 participants who had ever experienced the accident were male while 33.3 percent (95% CI: 26.5–40.1) of the participants were female. The average scores of their knowledge about traffic laws and riding safely were 6.2 (95% CI: 6.00-6.4) and 6.7 percent (95% CI: 6.52-6.94) respectively. In the aspect of circumstances in riding motorcycles, there were 80.5 percent of warning and banning signs, and 50.6 percent of frequently-broken traffic lights. 42.8 percent of the participants who had ever had the accident wore helmets every time they were riding motorcycles. 32 percent modified and decorated their motorcycles by slicing off their motorcycle seats. 36.9 percent were drunk while riding motorcycles. 40.2 percent had ever ridden through the red light. 69.4 percent rode the motorcycles with the speed of 51-80 km/hr. 80.5 percent rode their motorcycles without bringing their motorbike riding licenses. 52 percent used mobile phones while riding motorcycles. AIC technique used to study participating in preventing and solving the problems of road accidents resulting. After the projects, it was found that there were 3 factors causing accidents in Tamirum which were motorcycle riders, motorcycles and circumstances. The most essential factor was that riders did not respect traffic laws. According to the study, the problems and the ways to solve the problems were as followings. The solution of solving the problem of not wearing helmet while riding motorcycles was to choose the appropriate sizes of the helmets for the riders’ heads and the standard of helmets should meet Thai Industrial Standards Institute. The riders who were drunk while riding must be taught to raise their awareness by constructing the value of not drinking alcohol. Riding motorcycle with no motorbike riding licenses could be solved by having more strict regulations. Keywords: Behaviors of riding motorcycles, Participating in preventing and solving accident